Metaverse applications and supply chain innovation: Insights from text mining - Maryam Mahdikhani; Purushottam Lal Meena (Journal of Innovation & Knowledge (JIK), 2024)
This study explored the growing adoption of the Metaverse in the supply chain field, primarily focusing on topics discussed in news media and identifying the benefits of effective implementations. It further investigated whether disparities in these topics exist across various industries. Over 2,000 news articles, published in reputable global newspapers were collected using the LexisNexis online database to examine the applications of the Metaverse in supply chains. The study employed Latent Dirichlet Allocation (LDA) and BERTopic topic-modeling methodologies to identify prevalent topics within these articles. The results show that the BERTopic approach yields more coherent topics than the LDA approach. The most prominent topic identified was 'global supply chain growth amplified by digital technologies', highlighting the potential of the Metaverse to enhance financial growth across supply chains. The analysis also revealed that the Metaverse is being utilized across diverse sectors, including manufacturing, warehousing, logistics, retail, media, and mining. This study provided multi-faceted implications, extending beyond academic insights to offer tangible guidance for policymakers and industry leaders on the advantages and challenges of Metaverse implementation. This research contributed a fresh perspective to the existing literature by identifying key topics and successful implementations.
Keywords: C88; L80; O30; O39; 650; Metaverse; Virtual reality; Supply chain management; Topic modeling; Industry analysis